2005
DOI: 10.1111/j.1365-2141.2005.05476.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone involvement in sickle cell disease

Abstract: SummaryBone involvement is the commonest clinical manifestation of sickle cell disease both in the acute setting such as painful vasoocclusive crises, and as a source of chronic, progressive disability such as avascular necrosis. Management of these problems is often difficult because of the diagnostic imprecision of most laboratory and imaging investigations and because of the lack of evidence for most surgical procedures in sickle cell disease. This review first discusses the acute problems related to bone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
320
0
25

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(351 citation statements)
references
References 92 publications
6
320
0
25
Order By: Relevance
“…3,6,10 Bones may be affected by both hemolytic and vaso-occlusive processes in SCD. 2 In our study, we found a correlation between low BMD and increased erythropoietic activity, which was assessed by the strong correlation between LDH, reticulocytes and Hb levels.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…3,6,10 Bones may be affected by both hemolytic and vaso-occlusive processes in SCD. 2 In our study, we found a correlation between low BMD and increased erythropoietic activity, which was assessed by the strong correlation between LDH, reticulocytes and Hb levels.…”
Section: Discussionmentioning
confidence: 67%
“…Osteopenia and osteoporosis are often asymptomatic; however, pain, fractures, deformities, and vertebral collapse may occur and require chronic analgesia, mechanical support, and surgical interventions. [2][3][4][5][6] Several studies have shown an overall reduction of BMD in children with SCD. [7][8][9] The causes of BMD abnormalities in patients with SCD are probably Copyright ß 2011 CLINICS -This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http:// creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted noncommercial use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%
“…Those face a chronic disease, with onset in childhood leading to devastating consequences [1]. In spite of the impressive improvements in the survival of patients with SCD, scientific advances in chronic bone diseases are still lagging [12,13]. AVN, which refers to bone destruction due to subchondral oxygen deficiency, remains Journal of Hematology and Blood Disorders Volume 2 | Issue 1 the leading cause of crippling disability and the most common manifestation in patients with SCD [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Epiphyseal infarction has a predilection for the head of the femur (avascular necrosis), followed by the humorous, knee, and the small joints of the hands and feet (Jean-Baptiste and De Ceulaer, 2000;Lonergan et al, 2001). A significant number of HbSS patient develop epiphyseal osteonecrosis (Styles and Vichinsky, 1996;Ware et al, 1991), bone infection (Almeida and Roberts, 2005;Neonato et al, 2000), and transient red cell aplasia (abnormal decrease of reticulocytes) (Goldstein et al, 1987;Serjeant et al, 2001). …”
Section: Bone and Joint Complicationsmentioning
confidence: 99%